EVALUASI JOINT PROGRAM DI UNIT VERTIKAL TERKECIL OTORITAS PAJAK DAN OTORITAS PABEAN - Alan Afriyanto; Nisrina Widayuni (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2022)
The regulation about joint program in Ministry of Finance is only providing guidelines in The Head Office and Regional Office levels. The absence of guidelines for the smallest vertical unit has resulted in many Primary Tax Offices (PTO) and Customs and Excise Offices (CEO) Type C that have not carried out joint programs and loss a lot of potential revenue. This article is intended to examine the implementation of the joint program in the smallest vertical units. To examine, this articles uses a qualitative method with a case study approach. In-depth interviews, observations, and requests for various documents were conducted to collect data. The object of this research is Magelang PTO and Magelang CEO Type C. Based on data processing, the following conclusions are obtained. Magelang PTO and Magelang CEO Type C have not implemented a collaboration program. There are three challenges that have prevented the two offices from implementing the joint program, namely: the absence of guidelines for implementing joint programs in the smallest vertical units; there are cost and benefit considerations; there are different working areas. Beside that, based on the results from comparing data between excise payments and income tax payments, there is new potential revenue. Based on the research findings, policy makers in both agencies need to immediately formulate rules related to joint program for the smallest vertical units.